In vitro genotoxic study reinforces the use of titanium-35niobium alloy in biomedical implants - Dennia Perez de Andrade; Isabel Chaves Silva Carvalho; Bruno Henrique Godoi; Newton Soares da Silva; Carlos Alberto Alves Cairo; Cristina Pacheco Soares; Yasmin Rodarte Carvalho (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2020)
The applications of titanium based alloys are widely used as orthopedic implants due to their excellent combination of mechanical properties, corrosion resistance and outstanding biocompatibility. Recently studies have been demonstrated titanium-niobium alloys do not present cytotoxicity, exhibit corrosion resistance similar or superior to titanium and have elastic modulus significantly lower than other titanium alloys. These characteristics make these materials an alternative for several biomedical applications, mainly implants. Previous studies demonstrated that Ti-35Nb alloy exhibits the closest elastic modulus of bone, and have good performance in key parameters of osteogenesis, which means that this alloy has an excellent biological profile and shows a great potential for biomedical application. In the present study it was demonstrated that Ti-35Nb alloy did not present DNA damage. Thus, these results consolidate this alloy has a promising material to substitution to the materials currently used in orthopedics and in dentistry, with absence of cytotoxity and genotoxity.